The Deepwater Horizon oil spill - Bodden, Valerie (Bodden, Valerie. Disasters for all time., 2019)
Provides background information on oil drilling and famous oil spills, and presents the timeline of the "Deepwater Horizon" oil spill in 2010. Discusses what led to the explosion and resulting oil spill, the spill's deadly effects, and the disaster's legacy. Includes color photographs, a glossary, and further resources.